P27 Dance for people with chronic breathlessness: a feasibility study. (12th November 2019) - Harrison, SL; Bierski, K; Edwards, J; McFaull, V; McLusky, S; Russell, A; Williams, G; Williams, S
Abstract : Introduction and objectives: This programme investigates a dance activity for people living with chronic breathlessness. Pulmonary rehabilitation is a recommended component in its clinical management but uptake is poor. Our research with British Lung Foundation (BLF) 'Breathe Easy' support groups suggests that patients are put off by the unfamiliarity of the gym-like space and the language of 'pulmonary' and 'rehabilitation'. 1 Collaborative work with neuroscientists has revealed that people with chronic breathlessness have poor 'interoception' or bodily awareness. We propose that a dance programme would address these issues by providing exercise in more culturally familiar form, in a non-challenging space, and engaging the entire body. Methods: Collaborating with the BLF 'Breathe Easy' group in Darlington, UK, a local exercise instructor delivered dance over ten weeks mentored by a dance instructor. Functional exercise tolerance, balance and functional quadriceps strength were tested at baseline and after the ten-week programme using the six minute walk test, timed-up and go and 30 second sit to stand test respectively. Health status was assessed with the COPD Assessment Tool, and mood using the Patient Health Questionnaire-9 and Generalised Anxiety Disorder assessment-7. The Multidimensional Assessment of Interoceptive Awareness collected information on body awareness. A researcher was involved as participant-observer in the classes to assess the response of participants. Results: Ten people regularly participated in the programme. Initial quantitative outcomes point to the value of dancing together and keeping up with the beat; and participants reported 'coming alive'. Full results will be analysed when the programme completes on 29th July. We will report on the quantitative and qualitative results. Conclusions: Potential impacts to explore include: On the programme participants: enjoyment; any changes in physical and psychosocial outcomes, including interoception; acceptability of the intervention; exploration of an option beyond pulmonary rehabilitation to improve functional capacity and change breathlessness perception. On clinicians managing chronic breathlessness: This programme, if successful, may add to the range of options available. Reference: Oxley Rebecca, Harrison Samantha L., Rose Arthur, Macnaughton J. The meaning of 'pulmonary rehabilitation and its influence on engagement with individuals with chronic lung disease. Chronic Respiratory Disease 2019;16:1–9.